Analysis of the non-linear load and temperature-dependent creep behaviour of thermoplastic composite materials. (March 2017) - Brauner, Christian; Herrmann, Axel S; Niemeier, Philipp M; Schubert, Konstantin
Fibre-reinforced thermoplastic composite materials can be manufactured rapidly using a thermoforming process. The assortment of thermoplastic matrix systems is manifold and starts from bulk plastic like polypropylene (PP) up to high-performance systems like polyether ether ketone. High-performance thermoplastic polymers have durable properties but relatively high raw material costs. For structural application, engineering methods are needed to ensure the availability for use over the full range of the life cycle of parts. This equates to at least 15 years under exposure to varying climatic conditions for an automobile component. Bulk plastics have complex viscoelastic behaviour, which means that advanced methods are needed to ensure the long-term behaviour of both the pure plastic or fibre-reinforced materials with such a matrix system. In the following study, the creep behaviour of a glass fibre-reinforced PP material is investigated using different uniaxially loaded creep tests at different load and temperature levels. Starting from this empirical base, two characteristic creep functions are derived using a modified Burgers approach. To transfer the results of uniaxial creep situations to a three-dimensional multiaxial stress state, a method to interpolate the experimental creep curves is presented. This developed creep model is integrated into the implicit non-linear finite element program SAMCEF/Mecano and used to predict the creep behaviour of a complex laminate. The results are then validated against the performed experiments.